Orquestração de redes de inovação de comercialização no Brasil: dimensões, processos e proposição de um framework - Pereira, Muriel Garrido (Universidade do Vale do Rio dos Sinos, 2025)
This study aims to propose a framework for orchestrating innovation networks of the application/commercialization type in the Brazilian context. The research departs from the observation that, despite theoretical advancements, there is still no consensus on the dimensions, processes, and activities that should guide the orchestration of innovation networks. A qualitative exploratory approach was adopted, based on the Design Science Research (DSR) method, which enabled the iterative construction and validation of the artifact. The development of the framework occurred in four stages. First, a literature review was conducted, from which the initial framework (F0) was derived. Subsequently, three validation rounds were carried out with different groups of actors: academics, professionals engaged in innovation projects, and representatives of hubs. Each round provided insights that led to refinements, culminating in the final version (F3) of the framework. The findings indicate that the orchestration of innovation networks requires the consideration of multiple interdependent dimensions, ranging from actor mobilization to relationship management, including agenda alignment, knowledge flows, stabilization, governance, and administrative coordination. The analysis also highlights the relevance of conflict resolution processes, co-creation practices, and continuous alignment of objectives to ensure value creation for network members. From a practical standpoint, the framework offers managers and entrepreneurs a structured and adaptable model for application/commercialization networks in Brazil. From a theoretical perspective, the research advances the field by integrating different strands of literature and presenting an empirically validated model. Limitations are related to the focus on only one type of network and on the Brazilian context. Future studies are encouraged to expand the analysis to other types of networks and international settings.
Keywords: Orquestração de redes; Redes de inovação; Framework; Design science research; Aplicação/comercialização; Network orchestration; Innovation networks; Application/commercialization; ACCNPQ::Ciências Sociais Aplicadas::Administração